PENERAPAN MODEL PEMBELAJARAN PEROLEHAN KONSEP TERHADAP HASIL BELAJAR EKONOMI KELAS X1 - ROHMILAWATI ROHMILAWATI; YON RIZAL; NURDIN NURDIN (FKIP Unila, 2013)
Efforts that teachers can to create the learning process is transform the conventional learning,namely the acquisition of concept learning model.of acquisition models can improve learning Well as for the average Knowing Economics student outcomes is higher among which uses the concept of the learning model acquisition.tudent learning outcomes using the higher of the acquisition model of learning that does not use the concept of the learning model perolahan concept. This is evidenced by the results of tests using a model of learning that students gain higher draft obtained at 74.25, while the ability of students who did not use the model of learning with the acquisition of the concept of lower ability students gained 67.2 was followed by two test mean differences obtained ttab = 1.67 at significant level of 5% and 1% significance level obtained ttab = 2.39. From the results of these trials have shown that the average results of the economic study on students who were given high KonsepAcquisition application of economics to students' learning outcomes using methods or who does not use the conventional model of the acquisition of the concept of learning.Keywords: economic study results, the acquisition of the concept of the learning